Case report: Treatment of persistent atypical odontalgia with attention deficit hyperactivity disorder and autism spectrum disorder with risperidone and atomoxetine - Kasahara, Satoshi; Takao, Chihiro; Matsudaira, Ko; Sato, Naoko; Tu, Trang Thi Huyen; Niwa, Shin-Ichi; Uchida, Kanji; Toyofuku, Akira (Frontiers in Pain Research, 2022)
Chronic pain has recently been associated with developmental disorders [autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD)]. Regarding chronic pain in adulthood, fibromyalgia, migraine, and chronic low back pain have been associated with ADHD. The ICD-11 disease classification categorizes these pain diseases as chronic primary pain, suggesting high comorbidity with developmental disorders in chronic primary pain. Atypical odontalgia (AO) is a persistent tooth pain that occurs in the absence of any of the usual dental causes, most of which are triggered by dental treatment. Conditions characterized by tooth pain with no apparent cause are also classified as chronic primary pain. Approximately half the patients with AO are diagnosed with psychiatric disorders; the most common are depression (15.4%) and anxiety disorders (10.1%). However, there are no reports on neurodevelopmental disorders comorbid with AO. In the present study, we report a case of a 46-year-old man with numerous complaints (e.g., occlusal instability, difficulty eating, difficulty speaking), who took work leave due to worsening of his symptoms after periodontal scaling (“gingival recession” and “aggressive periodontal treatment”) and frequently expressed dissatisfaction and anger at the hospital, making the dental treatment difficult. After a referral to a psychiatrist specializing in chronic pain, AO and previously undiagnosed comorbidity of ASD and ADHD were confirmed. Atypical antipsychotic risperidone for ASD irritability and an ADHD medication, atomoxetine dramatically reduced anger, pain, anxiety, depression, and pain catastrophizing thoughts, leading to reduced obsession with his symptoms and less frequent complaints. After risperidone (1 mg/day) + atomoxetine (120 mg/day) were ultimately prescribed after adjustment, he was able to return to work 226 days after initiation of psychiatric treatment. Recent studies show that comorbidity of developmental disorders in patients with chronic pain is likely to be undetected. Clinicians should include screening for ASD and ADHD not only in cases of fibromyalgia, migraine, and chronic low back pain, but also in orofacial pain such as AO and other treatments for chronic primary pain. For patients diagnosed with ASD or ADHD, an effective drug therapy for ASD and ADHD should be considered.